1990
DOI: 10.1038/bjc.1990.19
|View full text |Cite
|
Sign up to set email alerts
|

A sequence previously identified as metastasis-related encodes an acidic ribosomal phosphoprotein, P2

Abstract: Summary We have used a metastasis-related human cDNA isolated from a liver metastasis from a colonic adenocarcinoma to screen a human breast carcinoma cDNA library for homologous sequences. Nucleotide sequence analysis of positive clones revealed that the cDNA represents a ribosomal phosphoprotein, P2. The expression of P2 mRNA was significantly higher (Student's t test, one tail; P.0.01) in seven fibroadenomas than in seven carcinomas, with an average five-fold difference. This enhanced expression level of P2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
15
1
1

Year Published

1991
1991
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 42 publications
4
15
1
1
Order By: Relevance
“…These data parallel our previous findings that the acidic ribosomal phosphoprotein P2 also has higher expression levels in the benign breast tumours (Sharp et al, 1990). In situ hybridisation has shown these genes to be expressed predominantly in the epithelium of breast tumours.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…These data parallel our previous findings that the acidic ribosomal phosphoprotein P2 also has higher expression levels in the benign breast tumours (Sharp et al, 1990). In situ hybridisation has shown these genes to be expressed predominantly in the epithelium of breast tumours.…”
supporting
confidence: 81%
“…We have isolated sequences with higher expression in the benign tissue (fibroadenoma) compared with the malignant tissue (carcinoma), and shown them to specify elongation factor-la (EF-1a) and human ubiquitin carboxyl extension protein (HUBCEP80); both proteins involved in translation. We have previously reported that the gene for another translation-associated protein, acidic ribosomal phosphoprotein P2, isolated as encoding a metastasis-related protein by Elvin et al (1988), has higher levels of RNA expression in benign tumours compared with malignant tumours (Sharp et al, 1990).…”
mentioning
confidence: 99%
“…The ribosomal proteins are thought to facilitate the folding and maintenance of an optimal configuration of the rRNAs (32), perhaps in this way conferring speed and accuracy on protein synthesis. Recently, the involvement of the ribosomal proteins in cell proliferation (33)(34)(35)(36)(37), differentiation (38), and apoptosis (39) has been demonstrated. It has been show that S10 protein can be cross-linked to eukaryotic initiation factor 3 (40), an observation suggesting that S10 protein forms part of the domain involved in binding of the initiation factor to the 40S subunit at the start of the translation (40).…”
Section: Discussionmentioning
confidence: 99%
“…The first one was isolated representing mRNA associated with tumor progression and metastasis in 1988 and was identified as RPP2 in 1990 [14,15]. RPL31 cDNA was selected from a normal colon cDNA library on the basis of overexpression in familial adenomatous polyposis (FAP).…”
Section: Ribosomal Proteins and Colorectal Car-cinomamentioning
confidence: 99%